SHM_120747_HST_3D Ceramic Pot - Bonnevier, Helena; National Historical Museums (National Historical Museums, 2026)
Photogrammetric 3D model of a ceramic pot from the Swedish Middle Ages, collected in the field from Slottsfjärden in Kalmar and held in the collections of the National Historical Museums in Stockholm.

Link to the Dynamic Collection platform

https://dyncoll.ht.lu.se/artifact_view.php?item=658

Link to Sök I Samlingarna

https://samlingar.shm.se/object/C8781A54-012D-4609-AF8A-8E0BEE01D4B0
Keywords: 3D Model; Museum Object; Archaeology; Archaeology; Photogrammetry; History and archaeology; Archaeology/history; Slottsfjärden; Swedish Middle Ages; Dynamic Collections; History and Archaeology; Historia och arkeologi; Archaeology; Arkeologi